Testing method for determining fracture surface energy of brittle material based on indentation feature size

By performing indentation experiments on brittle materials, measuring the indentation characteristic size and combining with the fracture surface energy calculation model, the problem of difficult and high cost of measuring the fracture surface energy of brittle materials in the prior art is solved, and a fast, accurate and low-cost testing method is achieved.

CN119574354APending Publication Date: 2025-03-07WUHAN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411605793.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art has problems such as difficult, high cost and complex operation when measuring the fractured surface energy of brittle materials, and cannot meet the actual testing needs.

Method used

Using a test method based on indentation feature size, the fracture surface energy calculation model is used to perform indentation experiments with different loads on the surface of brittle material samples, indentation microscopy pictures are collected, indentation feature size is measured, and the functional relationship between indentation feature size and load is obtained. Combined with the fracture surface energy calculation model, the fracture surface energy of the sample to be tested is calculated.

Benefits of technology

This method simplifies the sample preparation process, reduces the testing cost, improves the testing efficiency, and can quickly and accurately obtain the fracture surface energy of brittle materials, which is highly practical.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119574354A_ABST
    Figure CN119574354A_ABST
Patent Text Reader

Abstract

The invention discloses a test method for determining fracture surface energy of a brittle material based on indentation feature size, which comprises the following steps: executing indentation experiments with different loads, and collecting indentation microscopic pictures after the indentation experiments; measuring the feature size of the indentation according to the collected microscopic image of the indentation; fitting based on the measured indentation feature size and indentation load to obtain a function relation between the indentation feature size and the indentation load; and obtaining the fracture surface energy of the brittle material by combining a fracture surface energy model on the basis of the obtained function relation between the indentation feature size and the indentation load. The method for obtaining the fracture surface energy of the brittle material based on the indentation test can break through the limitation of a tensile test and a three-point bending beam test with a notch on the size and shape of a sample, and compared with a traditional method, the method is easy to operate, small in sample preparation difficulty, high in test efficiency, low in test cost, high in practicability and suitable for popularization and application. And the fracture surface energy of the brittle material can be rapidly and accurately obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material mechanical property measurement, in particular to the field of brittle material fracture surface energy measurement, and specifically to a testing method for determining the fracture surface energy of a brittle material based on an indentation characteristic size. Background Art

[0002] In engineering practice, when brittle materials fracture, they do not produce obvious deformation like ductile materials, which often leads to low-stress failure events when the working stress is less than the allowable stress. When the external stress impact on brittle materials is greater than the fracture strength, microcracks will occur in the brittle materials, leading to rupture. According to Griffith's microcrack theory, the fracture strength of the material is proportional to the square root of the fracture surface energy. In addition, fracture toughness is usually used as a criterion for the damage tolerance design of brittle materials in fracture mechanics. Fracture toughness is an important indicator to measure the material's resistance to crack extension, and fracture surface energy is an important parameter in fracture toughness measurement. Therefore, obtaining the fracture surface energy can guide structural design, which is of great significance for avoiding the frequent occurrence of low-stress failure events.

[0003] The existing technology often uses a stable tensile test and a three-point bending beam with a notch to measure the fracture surface energy of brittle materials. The stable tensile test can measure the load deformation curve, and the area under the curve is the fracture energy. This method of directly measuring the fracture energy is very difficult and ignores the energy absorbed by the elastic deformation of the indenter and the support. The three-point bending beam test method with a notch is easy to operate and has high accuracy, but it is difficult and costly to process the specimen notch, so it cannot be widely used.

[0004] At present, there is an urgent need to comprehensively consider the actual testing needs in multiple aspects such as test cost, experimental feasibility and test accuracy, and propose a more effective and low-cost test method for measuring the fracture surface energy of brittle materials. Summary of the invention

[0005] In order to overcome the deficiencies of the above-mentioned prior art, the present invention provides a testing method for determining the fracture surface energy of brittle materials based on the characteristic size of indentation. The method has the advantages of simple sample preparation, high testing efficiency and low overall cost, so as to overcome the deficiencies in the existing testing methods for the fracture surface energy of brittle materials.

[0006] According to one aspect of the present invention, a test method for determining the fracture surface energy of a brittle material based on an indentation characteristic size is provided, comprising:

[0007] Perform indentation tests with different loads on the surface of the brittle material sample to be tested, and collect indentation micrographs after the indentation test;

[0008] According to the collected indentation microscopic pictures, measure the characteristic size of the indentation;

[0009] Based on the indentation characteristic size and the indentation load, a functional relationship between the indentation characteristic size and the indentation load is obtained by fitting;

[0010] Based on the obtained functional relationship between the indentation characteristic size and the indentation load, combined with the fracture surface energy calculation model, the fracture surface energy of the sample to be tested is calculated.

[0011] As a further technical solution, the method for preparing the brittle material sample to be tested is:

[0012] Cut the brittle material so that the size of the cut brittle material meets the preset size of the indentation test;

[0013] Mount the samples using epoxy resin;

[0014] The surface of the test sample is mechanically ground and polished to make the surface roughness of the test sample meet the indentation test standard.

[0015] As a further technical solution, the method further includes: performing an indentation test with no less than 5 loads on the surface of the brittle material sample to be tested, and the selection of the indentation test load needs to cause the brittle material to deform and cause crack extension.

[0016] As a further technical solution, the measuring of the characteristic size of the indentation based on the collected microscopic image of the indentation includes: measuring the diagonal length of the indentation and the length of the surface crack.

[0017] As a further technical solution, the functional relationship between the indentation characteristic size and the indentation load obtained by fitting is:

[0018] ;

[0019] Where, F is the indentation load; a is the diagonal length of the indentation; and c is the surface crack length.

[0020] As a further technical solution, the fracture surface energy calculation model is:

[0021] ;

[0022] Among them, γ is the fracture surface energy; λ is a constant related to the shape of the residual indentation mark projection area; δ is a dimensionless constant; F is the indentation load; a is the indentation diagonal length; c is the surface crack length; χ is a dimensionless constant related to the material Poisson's ratio ν.

[0023] According to one aspect of the present invention, there is provided a testing system for determining the fracture surface energy of a brittle material based on an indentation characteristic size, comprising an indentation test device and a data processing device, wherein:

[0024] The indentation test equipment is used to perform indentation tests with different loads on the surface of the brittle material sample to be tested, collect indentation micrographs after the indentation test, and measure the indentation characteristic size based on the collected indentation micrographs;

[0025] The data processing device is used to fit the functional relationship between the indentation characteristic size and the indentation load based on the indentation characteristic size and the indentation load, and calculate the fracture surface energy of the sample to be tested based on the obtained functional relationship between the indentation characteristic size and the indentation load in combination with the fracture surface energy calculation model.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] 1. The fracture surface energy of brittle materials obtained by the present invention based on classical fracture mechanics theory has high accuracy and credibility, and is a useful supplement to conventional fracture surface energy testing methods.

[0028] 2. The method for obtaining the fracture surface energy of brittle materials based on indentation testing proposed in the present invention can break through the limitations of tensile tests and three-point bending beam tests with incisions on sample size and shape. Compared with traditional methods, this method is simple to operate, has low sample preparation difficulty, high testing efficiency, low testing cost, and strong practicality, and can quickly and accurately obtain the fracture surface energy of brittle materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, a brief introduction is given below to the drawings used in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0030] Figure 1 A schematic flow chart of a test method for determining the fracture surface energy of a brittle material based on the characteristic size of an indentation provided in an embodiment of the present invention.

[0031] Figure 2 The test method for determining the fracture surface energy of a brittle material based on the characteristic size of the indentation provided in an embodiment of the present invention includes a microscopic image of the indentation collected after an indentation experiment using a Berkovich indenter and a schematic diagram of the marked characteristic size of the indentation.

[0032] Figure 3 The test method for determining the fracture surface energy of a brittle material based on the characteristic size of the indentation provided in an embodiment of the present invention includes a microscopic image of the indentation collected after an indentation experiment using a Vickers indenter and a schematic diagram of the marked characteristic size of the indentation.

[0033] Figure 4A graph showing the relationship between indentation feature size and indentation load in a test method for determining fracture surface energy of brittle materials based on indentation feature size provided in an embodiment of the present invention. DETAILED DESCRIPTION

[0034] The terms "including" and "having" and any variations thereof in the specification and claims of the present invention and the above-mentioned drawings are intended to cover non-exclusive inclusions, for example, a process, method, system, product or apparatus comprising a series of steps or units is not necessarily limited to the steps or units explicitly listed, but may include other steps or units not explicitly listed or inherent to these processes, methods, products or apparatuses.

[0035] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. In addition, the technical features in the various embodiments or single embodiments provided by the present invention are arbitrarily combined with each other to form a new technical solution. This combination is not restricted by the sequence of steps and / or the structural composition mode, but must be based on the ability of ordinary technicians in this field to achieve. When the combination of technical solutions is contradictory or cannot be achieved, it should be considered that this combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0036] The embodiment of the present invention provides a testing method for determining the fracture surface energy of a brittle material based on the characteristic size of an indentation, such as Figure 1 As shown, including:

[0037] Step 1, performing an indentation test with different loads on the surface of the brittle material sample to be tested, and collecting an indentation micrograph after the indentation test;

[0038] Step 2, measuring the characteristic size of the indentation according to the collected microscopic image of the indentation;

[0039] Step 3, based on the indentation characteristic size and the indentation load, fitting to obtain a functional relationship between the indentation characteristic size and the indentation load;

[0040] Step 4: Based on the obtained functional relationship between the indentation characteristic size and the indentation load, combined with the fracture surface energy calculation model, the fracture surface energy of the brittle material is obtained.

[0041] The sample to be tested is silicon carbide, and the preparation method of the sample to be tested is:

[0042] 1) Cut the brittle material so that the size of the cut brittle material meets the preset size of the indentation test;

[0043] 2) Use epoxy resin to mount the sample to facilitate grinding and polishing;

[0044] 3) Mechanically grind and polish the surface of the test sample to make the surface roughness of the test sample meet the indentation test standard.

[0045] During polishing, the silicon carbide surface is first ground with low-grit sandpaper, then polished with high-grit sandpaper, and finally deeply polished with diamond suspensions of different particle diameters to make the surface roughness meet the indentation test standard.

[0046] During the test, the indentation test load requirement is: perform indentation tests with no less than 5 loads on the surface of the brittle material, and the selection of the indentation test load must cause the brittle material to deform and crack to extend. This is used for function fitting in step 3.

[0047] The indentation test can use a Berkovich indenter or a Vickers indenter. Place the prepared silicon carbide sample on the sample stage of the Anton Paar nanoindenter, use the Berkovich indenter to perform indentation tests on the silicon carbide surface under different loads (1~500 mN), and collect microscopic images after the indentation test in real time, such as Figure 2 shown.

[0048] According to the collected indentation microscopic images, measure the characteristic size of the indentation, including: measuring the indentation diagonal length and the surface crack length. In step 2, use Image J software to measure the indentation diagonal length a and the surface crack length c according to the collected indentation microscopic images, such as Figure 2 shown.

[0049] In step 3, use Origin software to fit Fa 2 and c 3 The relationship curve, such as Figure 4 As shown in the figure, the functional relationship between the indentation feature size and the indentation load is:

[0050] ;

[0051] Where, F is the indentation load; a is the diagonal length of the indentation; and c is the surface crack length.

[0052] The derivation method of the fracture surface energy calculation model is as follows:

[0053] According to fracture mechanics theory, the fracture toughness K of brittle materials c The calculation formula is expressed as:

[0054] ;

[0055] Where E is the elastic modulus; γ is the fracture surface energy; χ is a dimensionless constant; it can be expressed as: , ν is the Poisson's ratio of the sample.

[0056] Specifically, the empirical relationship between the indentation crack size and the indentation load F of brittle materials is introduced:

[0057] ;

[0058] Where δ is a dimensionless constant, which is 0.024 and 0.016 for Berkovich and Vickers indenters, respectively. H is the indentation hardness, which is defined as the ratio of the indentation load F to the indentation projected area A:

[0059] ;

[0060] Where λ is a constant related to the shape of the residual indentation projection area. For the Berkovich indenter, λ = , for Vickers head, λ=2.

[0061] Therefore, the fracture surface energy calculation model, that is, the calculation formula of the fracture surface energy γ of brittle materials can be expressed as:

[0062] .

[0063] For silicon carbide, the Poisson's ratio recorded in the literature (M Nuruzzaman, MA Islam, MA Alam, MAH Shah, AMM TKarim, Structural, elastic and electronic properties of 2H- and 4H-SiC. International Journal of Engineering Research and Applications, 2015, 5:48-52) is 0.157, so χ = =1.432.

[0064] Set λ = , δ=0.024, χ=1.432, and the relationship obtained by fitting in step 3, namely Fa 2 =19.5c 3 , substitute into the derived brittle material fracture surface energy calculation model.

[0065] The fracture surface energy of silicon carbide calculated by the method of the present invention is 7.1 J / m2, which is close to the fracture surface energy of 7.5 J / m2 recorded in the open literature (Lawn B, translated by Gong Jianghong, Fracture Mechanics of Brittle Solids, pages 44 and 45; Li Yuanyuan, Yu Yin, Meng Chuanmin, Zhang Lu, Wang Tao, Li Yongqiang, He Hongliang, He Duanwei. Impact strength of diamond-silicon carbide superhard composites, Acta Physica Sinica, 2019, 68:317-323), with an error of 5.1%, which is within the acceptable range for engineering.

[0066] The implementation basis of each embodiment of the present invention is to implement programmed processing through a device with a processor function. Therefore, in engineering practice, the technical solutions and functions of each embodiment of the present invention are encapsulated into various modules. Based on this reality, on the basis of the above embodiments, an embodiment of the present invention provides a test system for determining the fracture surface energy of a brittle material based on the characteristic size of an indentation, and the system is used to execute the test method for determining the fracture surface energy of a brittle material based on the characteristic size of an indentation in the above method embodiment.

[0067] A test system for determining the fracture surface energy of a brittle material based on an indentation characteristic size includes an indentation test device and a data processing device, wherein the indentation test device is used to perform an indentation test with different loads on the surface of a brittle material sample to be tested, collect an indentation microscopic picture after the indentation test, and measure the indentation characteristic size according to the collected indentation microscopic picture; the data processing device is used to fit the functional relationship between the indentation characteristic size and the indentation load based on the indentation characteristic size and the indentation load, and calculate the fracture surface energy of the sample to be tested based on the obtained functional relationship between the indentation characteristic size and the indentation load, combined with a fracture surface energy calculation model. The test system for determining the fracture surface energy of a brittle material based on the indentation characteristic size provided by an embodiment of the present invention measures the indentation characteristic size by performing an indentation test with different loads, and fits the functional relationship between the indentation characteristic size and the indentation load, and calculates the fracture surface energy of the brittle material by combining a fracture surface energy model. Compared with the traditional method, the method is simple to operate, has low sample preparation difficulty, high test efficiency, low test cost, and strong practicality, and can achieve rapid and accurate acquisition of the fracture surface energy of brittle materials.

[0068] It should be noted that the system embodiment provided by the present invention is used to implement the methods in the above method embodiment as well as the methods in other method embodiments provided by the present invention. The only difference is that the corresponding functional modules are set. The principle is basically the same as the principle of the above system embodiment provided by the present invention. As long as the technical personnel in this field refer to the specific technical solutions in other method embodiments on the basis of the above system embodiment, obtain the corresponding technical means and the technical solutions composed of these technical means by combining the technical features, and on the premise of ensuring the practicality of the technical solutions, improve the modules in the above system embodiment to obtain the corresponding system class embodiments, which are used to implement the methods in other method class embodiments. For example:

[0069] Based on the contents of the above system embodiment, as a preferred embodiment, the test system for determining the fracture surface energy of a brittle material based on the characteristic size of an indentation provided in the embodiment of the present invention, the sample to be tested is silicon carbide, and the preparation method of the sample to be tested is:

[0070] Cut the brittle material so that the size of the cut brittle material meets the preset size of the indentation test;

[0071] Mount the samples using epoxy resin;

[0072] The surface of the test sample is mechanically ground and polished to make the surface roughness of the test sample meet the indentation test standard.

[0073] Based on the contents of the above system embodiments, as a preferred embodiment, a testing system for determining the fracture surface energy of a brittle material based on the characteristic size of an indentation is provided in an embodiment of the present invention, and the method further includes: performing an indentation test with no less than 5 loads on the surface of the brittle material sample to be tested.

[0074] Based on the contents of the above system embodiments, as a preferred embodiment, in the test system for determining the fracture surface energy of brittle materials based on the characteristic size of the indentation provided in the embodiments of the present invention, the characteristic size of the indentation is measured according to the collected indentation microscopic images, including: measuring the diagonal length of the indentation and the length of the surface crack.

[0075] Based on the contents of the above system embodiment, as a preferred embodiment, in the test system for determining the fracture surface energy of brittle materials based on the indentation characteristic size provided in the embodiment of the present invention, the functional relationship between the indentation characteristic size and the indentation load obtained by fitting is:

[0076] ;

[0077] Where, F is the indentation load; a is the diagonal length of the indentation; and c is the surface crack length.

[0078] Based on the content of the above system embodiment, as a preferred embodiment, in the test system for determining the fracture surface energy of brittle materials based on the characteristic size of the indentation provided in the embodiment of the present invention, the fracture surface energy calculation model is:

[0079] ;

[0080] Among them, γ is the fracture surface energy; λ is a constant related to the shape of the residual indentation mark projection area; δ is a dimensionless constant; F is the indentation load; a is the indentation diagonal length; c is the surface crack length; χ is a dimensionless constant related to the material Poisson's ratio ν.

[0081] In summary, the present invention performs indentation experiments with different loads, measures the characteristic size of the indentation, and obtains the functional relationship between the characteristic size of the indentation and the indentation load by fitting, and combines the fracture surface energy model to calculate the fracture surface energy of the brittle material. Compared with the traditional method, this method is simple to operate, has low sample preparation difficulty, high test efficiency, low test cost, strong practicality, and can achieve rapid and accurate acquisition of the fracture surface energy of the brittle material.

[0082] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the technical solutions of the embodiments of the present invention.

Claims

1. A test method for determining the fracture surface energy of brittle materials based on the characteristic size of indentation, characterized in that: include: Perform indentation tests with different loads on the surface of the brittle material sample to be tested, and collect indentation micrographs after the indentation test; According to the collected indentation microscopic pictures, measure the characteristic size of the indentation; Based on the indentation characteristic size and the indentation load, a functional relationship between the indentation characteristic size and the indentation load is obtained by fitting; Based on the obtained functional relationship between the indentation characteristic size and the indentation load, combined with the fracture surface energy calculation model, the fracture surface energy of the sample to be tested is calculated.

2. The test method for determining the fracture surface energy of brittle materials based on the characteristic size of indentation according to claim 1, characterized in that: The preparation method of the brittle material sample to be tested is: Cut the brittle material so that the size of the cut brittle material meets the preset size of the indentation test; Mount the samples using epoxy resin; The surface of the test sample is mechanically ground and polished to make the surface roughness of the test sample meet the indentation test standard.

3. The test method for determining the fracture surface energy of brittle materials based on the characteristic size of indentation according to claim 1, characterized in that: The method further comprises: performing an indentation test with no less than 5 loads on the surface of the brittle material sample to be tested.

4. The test method for determining the fracture surface energy of brittle materials based on the characteristic size of indentation according to claim 1, characterized in that: According to the collected indentation micrographs, the characteristic dimensions of the indentation are measured, including: measuring the diagonal length of the indentation and the length of the surface crack.

5. The test method for determining the fracture surface energy of brittle materials based on the characteristic size of indentation according to claim 4, characterized in that: The functional relationship between the indentation characteristic size and the indentation load obtained by fitting is: ; Where, F is the indentation load; a is the diagonal length of the indentation; and c is the surface crack length.

6. The test method for determining the fracture surface energy of brittle materials based on the characteristic size of indentation according to claim 5, characterized in that: The fracture surface energy calculation model is: ; Among them, γ is the fracture surface energy; λ is a constant related to the shape of the residual indentation mark projection area; δ is a dimensionless constant; F is the indentation load; a is the indentation diagonal length; c is the surface crack length; χ is a dimensionless constant related to the material Poisson's ratio ν.

7. A test system for determining the fracture surface energy of brittle materials based on indentation characteristic dimensions, comprising an indentation test device and a data processing device, characterized in that: include: The indentation test equipment is used to perform indentation tests with different loads on the surface of the brittle material sample to be tested, collect indentation micrographs after the indentation test, and measure the indentation characteristic size based on the collected indentation micrographs; The data processing device is used to fit the functional relationship between the indentation characteristic size and the indentation load based on the indentation characteristic size and the indentation load, and calculate the fracture surface energy of the sample to be tested based on the obtained functional relationship between the indentation characteristic size and the indentation load in combination with the fracture surface energy calculation model.

Citation Information

Patent Citations

  • In-situ synchronous test method and device for fracture toughness and residual stress of fragile material

    CN104075941A

  • Method for quantitative detection of indentation fracture toughness of coating material

    CN109406280A

  • Method and Apparatus for Residual Stress Measurement Through Indentation with In-situ Generated Reference

    US20160282246A1

  • Method for evaluating fracture toughness using instrumented indentation testing

    US9702798B1